Mineralogy of Duné s Sand of Missan Dune Fields Southeastern Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The aim of this study is to define the mineralogical composition of Missan dune fields South Eastern of Iraq, and try to determine the origin or the source of these dunes .Three main types of dunes were recognized in the studied area, these are: barchanoid ridge, barchans and nabkha dunes. The direction of these dunes is northwest to southeast.The dunes in Missan dune fields were divided into three fields according to the vari- eties in the composition and geographical position in the studied area, these three fields are: Al-Manziliyah, Middle Chailat, and Said Subair dune fields.9 samples were collected from these fields, the samples were separated into light and heavy fraction by heavy liquids. The light fraction composed from quartz, feldspar, and rock fragments, the rock fragments composed mainly of carbonate, chert, igneous, and metamorphic rock fragments .The heavy minerals are mostly opaques, chlorite, pyroxenes, amphiboles, epidotes, zircon, garnet, muscovite, biotite, kyanite, staurolite, and rutile .The percentages of heavy minerals fraction to light minerals fraction was very vari- able in which the percentage of heavy minerals in Sayid Subair field are higher than the percentage in Al-Manziliyah field.The source area of these sediments is the recent sed- iment that deposited in the flood plain and traces of the Tigris river and the outcrops    of upper Miocene-Pliocene rocks in the eastern of studied area (Himreen Anticline and Zagros Mountain).